Welding defects classification through a Convolutional Neural Network. (January 2023) - Perri, Stefania; Spagnolo, Fanny; Frustaci, Fabio; Corsonello, Pasquale
Abstract: This letter presents a Convolutional Neural Network (CNN), named WelDeNet, customized to classify welding defects, such as lack of penetration (LP), cracks (CR), porosity (PO) and no defect (ND), by inspecting digitalized radiographic images. A new dataset that collects 24, 407 images representing welding defects is also presented. WelDeNet consists of 14 cascaded convolutional layers and achieves a test accuracy of 99.5 %. When hardware implemented within the Raspberry Pi 3B + board, WelDeNet exhibits an inference time of only 134 ms, with CPU and memory utilizations of just 51 % and 47 MB, thus offering a promising solution easy-to-integrate in a real industrial environment.